Lernerfahrungen im Feld der Komparativen Theologie. Ein Werkstattbericht - Stosch, Klaus von 1971- (2024)
Comparative theology originally developed from the encounter with Eastern religions. As a result, it lacks concrete theological discussions with other religions in their theological self-understanding. While the theology of Israel has seemingly always been a breaking point for all theologies of religions, the article aims to show that Qurʾanic theology also holds its own challenges for Christianity, which must be addressed in contemporary comparative theological research. Especially the insight that many Qurʾanic interventions in Christological debates are dependent on a critique of the imperial political theology of Byzantium challenges traditional views on Muslim-Christian relations. But also recent ecumenical approaches to the Qurʾanic theology of Abrahamic religions have to be reflected.